Political activism as a determinant of clientelistic transfers: Evidence from an Indian public works program - Chau, Nancy H.; Liu, Yanyan; Soundararajan, Vidhya (International Food Policy Research Institute, 2017)
This paper contributes to the literature by developing a model of political clientelism based on an under-explored citizen attribute - political activism, in addition to two other attributes: political affiliation and income. The model uncovers the role of "politically active" individuals in their ability to influence and shape opinion, as well as the inclination of politicians to offer targeted transfers to this group in order to indirectly influence other voters (ie., activists or undecided voters).